Agriculturally Relevant Climate Extremes and Their Trends in the World's Major Growing Regions. Issue 4 (30th April 2018) - Zhu, Xiao; Troy, Tara J.
Abstract: Climate extremes can negatively impact crop production, and climate change is expected to affect the frequency and severity of extremes. Using a combination of in situ station measurements (Global Historical Climatology Network's Daily data set) and multiple other gridded data products, a derived 1° data set of growing season climate indices and extremes is compiled over the major growing regions for maize, wheat, soybean, and rice for 1951–2006. This data set contains growing season climate indices that are agriculturally relevant, such as the number of hot days, duration of dry spells, and rainfall intensity. Before 1980, temperature‐related indices had few trends; after 1980, statistically significant warming trends exist for each crop in the majority of growing regions. In particular, crops have increasingly been exposed to extreme hot temperatures, above which yields have been shown to decline. Rainfall trends are less consistent compared to temperature, with some regions receiving more rainfall and others less. Anomalous temperature and precipitation conditions are shown to often occur concurrently, with dry growing seasons more likely to be hotter, have larger drought indices, and have larger vapor pressure deficits. This leads to the confluence of a variety of climate conditions that negatively impact crop yields. These results show a consistent increase in global agricultural exposure to negative climate conditions since 1980. Key Points: Agriculturally focused, historical climate data set is derived to assess agricultural climate risk An acceleration in warming trends, including extreme heat exposure, has occurred since 1980 over the major growing regions for wheat, maize, soybean, and rice Warming trends are accompanied by trends in drought indices and vapor pressure deficit, both of which may have deleterious impacts on crop yields